STUDI EKSPERIMENTAL: ANALISA KEGAGALAN RODA GIGI PADA GEAR BOX MESIN SCREW PRESS KELAPA SAWIT - Krisna, Pratama Pela; ., Taufikurahman; Sundari, Ella (Politeknik Negeri Sriwijaya, Indonesia, 2020)
The gear is a connecting component or power transmission of a machining process, if there is damage to the gears of an engine then this results in the inability to work on a machine. In this study, the damage to the gear of the screw press was broken and split so that several tests were used, namely the hardness test, the metallographic test and the composition test. The results showed that the damage occurred due to the lack of hardness in the gear where the hardness value of the screw press gear was 144.457 kg / mm² while the minimum hardness based on ASTM A291 was around 170-230 kg / mm². In the metallographic test, it can also be seen that there are cracks in the material structure of the screw press gear which causes the teeth to break and split. The composition test was carried out and it was found that the gear material contained a high enough carbon element, namely 5.05%, with this carbon value it could be concluded that the type of gear material for the screw press machine was cast iron with the addition of several alloys. Keywords: Gears, Screw Press machine, Gear Box, Brinnel-Test, Metallography